2015
DOI: 10.1111/ecc.12348
|View full text |Cite
|
Sign up to set email alerts
|

From a reactive to a proactive safety approach. Analysis of medication errors in chemotherapy using general failure types

Abstract: A better understanding of why medication errors (MEs) occur will mean that we can work proactively to minimise them. This study developed a proactive tool to identify general failure types (GFTs) in the process of managing cytotoxic drugs in healthcare. The tool is based on Reason's Tripod Delta tool. The GFTs and active failures were identified in 60 cases of MEs reported to the Swedish national authorities. The most frequently encountered GFTs were defences, procedures, organisation and design. Working condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Additionally, it has been found that a considerable portion of serious safety incidents related to medicine dispensing are highly preventable . Accordingly, contemporary views of medication safety emphasize the need of timely identification of systemic weaknesses and their proactive correction rather than a hindsight reaction, after the actual error has already been committed . Therefore, the research focus in this area has shifted from basic, epidemiological studies on the incidence of dispensing errors to prospective risk analyses, enabling decisive changes to be implemented before harm occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been found that a considerable portion of serious safety incidents related to medicine dispensing are highly preventable . Accordingly, contemporary views of medication safety emphasize the need of timely identification of systemic weaknesses and their proactive correction rather than a hindsight reaction, after the actual error has already been committed . Therefore, the research focus in this area has shifted from basic, epidemiological studies on the incidence of dispensing errors to prospective risk analyses, enabling decisive changes to be implemented before harm occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, chemotherapy administration is considered one of the most risky and challenging treatments in medicine. ’A range of studies conducted in France, Canada, United States, and Sweden identified missed doses and failure to deliver results on laboratory tests required to start treatment as common chemotherapy administration errors (Ranchon et al, 2011, White et al, 2014, Chera et al, 2015, Fyhr and Ternov, 2017). In the Arab countries context, literature revealed a single study which was conducted in Egypt and identified that undetermined cancer staging in the treatment plan (68%) and dose errors (66%) were the common causes of chemotherapy administration errors (Barakat et al, 2016).…”
Section: Introductionmentioning
confidence: 99%